Seleção e caracterização de Trichogramma (Hymenoptera: Trichogrammatidae) em Duponchelia fovealis Zeller (Lepidoptera: Crambidae) - Paes, João Paulo Pereira (2015)
The strawberry is a herbaceous climbing plant and perennial Rosaceae family, being produced and appreciated in various regions of the world. However, the production system of this vegetable crop is commonly affected by arthropod pests. In Brazil, in addit